Analysis of Factors Affecting Tourist Visits in Karo Regency - Sembiring, Mutiara Natasa; Nasution, Harmein; Sugiharto (Jurnal Sistem Teknik Industri, 2023)
Indonesia is a country that has various natural and cultural resources that can be utilized for tourism. Natural wealth which includes natural tourism, cultural tourism, and others exists in various regions in Indonesia, one of which is Karo Regency. Karo Regency is able to become a tourist destination that can attract tourists to visit. However, in recent years the level of tourist visits has decreased. Therefore, it is necessary to know what factors influence the interest in visiting tourists so that it can be an evaluation for the government to increase tourist visits. This research was conducted by analyzing three influencing variables, namely service quality, tour packages and tourist facilities with data analysis using the Structural Equation Modeling (SEM) method. Based on the results of data analysis it is known that these three variables have a positive effect on increasing interest in tourist visits. Thus, recommendations can be given that can be carried out by the government or the local community by taking into account these three variables.